Dude, you're a fag: masculinity and sexuality in high school : with a new preface - Pascoe, C. J. (University of California Press, 2012)
"High school and the difficult terrain of sexuality and gender identity are brilliantly explored in this smart, incisive ethnography. Based on eighteen months of fieldwork in a racially diverse working-class high school, Dude, You're a Fag sheds new light on masculinity both as a field of meaning and as a set of social practices. C.J. Pascoe's unorthodox approach analyzes masculinity as not only a gendered process but also a sexual one. She demonstrates how the 'specter of the fag' becomes a disciplinary mechanism for regulating heterosexual as well as homosexual boys and how the 'fag discourse' is as much tied to gender as it is to sexuality"–Provided by publisher.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; adolescents*; amériques; approches et analyses; californie; cours; discipline; ethnographie; hétérosexisme; masculinité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Concepts fondamentaux pour les études de genre - Roventa-Frumusani, Daniela (Agence universitaire de la francophonie, 2009)
C'est dans la perspective de l'amélioration du sort de la moitié de l'humanité que nous avons conçu ce lexique fondamental expliquant la genèse et le fonctionnement de la violence, du travail, de l'inégalité conjuguées au féminin, dans l'espoir que les jeunes générations y réfléchiront et agiront en famille, sur le marché du travail, dans l'agora et les médias. Nous espérons que ce regard (sociologique, historique, méthodologique) sur la situation des femmes contribuera à l'approfondissement de la connaissance et compréhension de nombreuses problématiques concernant " le monde des femmes ", ainsi qu'à la dissolution de ce que Pierre Bourdieu appelle la violence symbolique, exercée essentiellement par les voies symboliques de la communication et de la connaissance, ou plus exactement de la méconnaissance qui a transformé l'histoire en nature et l'arbitraire culturel en naturel. Nous avons essayé aussi de tisser des liens entre les champs des recherches produites dans le monde francophone et celui anglophone, liens absolument indispensable dans la société contemporaine mondialisée. Nous estimons que cet ouvrage sera utile à tous ceux / celles interpellées par les grands problèmes du monde contemporain et désireux de participer au changement social. Les philosophes ont interprété le monde, disait Marx, mais l'important c'est de le changer ; et on peut le changer en comprenant le passé et le présent afin de préparer l'avenir.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; genre; histoire; identités LGBTQIA2+; inégalités; patriarcat; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales

Thinking straight: the power, the promise, and the paradox of heterosexuality - Ingraham, Chrys (Routledge, 2005)
This collection of original essays will unravel the current heterosexual scene in two parts: one on rights and privileges, the other on popular culture. Topics covered include weddings, proms, citizenship, marriage penalties, cartoons, mermaids and myth.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; hétérosexualité; mariage; patriarcat; premier cycle; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques